Recent Progress in Lithium Niobate: Optical Damage, Defect Simulation, and On‐Chip Devices. Issue 3 (7th July 2019) - Kong, Yongfa; Bo, Fang; Wang, Weiwei; Zheng, Dahuai; Liu, Hongde; Zhang, Guoquan; Rupp, Romano; Xu, Jingjun
Abstract: Lithium niobate (LN) is one of the most important synthetic crystals. In the past two decades, many breakthroughs have been made in material technology, theoretical understanding, and application of LN crystals. Recent progress in optical damage, defect simulation, and on‐chip devices of LN are explored. Optical damage is one of the main obstacles for the practical usage of LN crystals. Recent results reveal that doping with ZrO2 not only leads to better optical damage resistance in the visible but also improves resistance in the ultraviolet region. It is still awkward to extract defect characteristics and their relationship with the physical properties of LN crystals directly from experimental investigations. Recent simulations provide detailed descriptions of intrinsic defect models, the site occupation of dopants and the variation of energy levels due to extrinsic defects. LN is considered to be one of the most promising platforms for integrated photonics. Benefiting from advances in smart‐cut, direct wafer bonding and layer transfer techniques, great progress has been made in the past decade for LNs on insulators. Recent progress on on‐chip LN micro‐photonic devices and nonlinear optical effects, in particular photorefractive effects, are briefly reviewed. Abstract : Lithium niobate (LN) is often dubbed as the "silicon of nonlinear optics" or "silicon of photonics". It has played a prominent role in many breakthroughs in the past two decades. An overview of recent progress in optical damage, defect simulation, and on‐chip devices of LN is presented, and nonlinear optical effects, in particular photorefractive effects, are briefly reviewed.